2009
DOI: 10.1158/1078-0432.ccr-08-2641
|View full text |Cite
|
Sign up to set email alerts
|

CCL22 Recruits CD4-positive CD25-positive Regulatory T Cells into Malignant Pleural Effusion

Abstract: Purpose: The aim of this study was to explore the presence of the chemokines CCL22 and CCL17 in malignant pleural effusion, and the chemoattractant activity of these chemokines on CD4-positive CD25-positive Foxp3-positive regulatory Tcells infiltrating into the pleural space. Experimental Design: The concentrations of CCL22 and CCL17 in both pleural effusions and sera from 33 patients with lung cancer were determined. Flow cytometry was done to determine T lymphocyte subsets in cell pellets of pleural effusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 26 publications
(2 reference statements)
2
59
0
3
Order By: Relevance
“…CCL22 was associated with increased frequency of Tregs in tumor-infiltrating lymphocytes in gastric cancer (9). Interestingly, intrapleural administration of CCL22 of patients produced a marked progressive influx of Tregs into pleural space (10). These data suggest that chemokine could induce Tregs migration to the pleural space.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…CCL22 was associated with increased frequency of Tregs in tumor-infiltrating lymphocytes in gastric cancer (9). Interestingly, intrapleural administration of CCL22 of patients produced a marked progressive influx of Tregs into pleural space (10). These data suggest that chemokine could induce Tregs migration to the pleural space.…”
Section: Introductionmentioning
confidence: 81%
“…Qin and colleagues (10) found that CCL22 can recruit Tregs into MPE. However, their further study indicated that the recruitment of Tregs by CCL22 also exists in pleural effusion of tuberculosis (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference might be caused by the levels of some cytokines in tumor tissues and malignant fluids. Although many studies have characterized the changes of immune microenvironment through recruitment of leukocytes induced by chemokines, [35][36][37][38][39] it could be also important to elucidate the relation between expansion of T cell clonotypes and expression of chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…CCL22 function is the effect on Treg homeostasis in that CCL17, but not CCL22 had been shown to modulate Treg function through its effect on dendritic cells, while CCL22 has been shown to play a more dominant role in Treg recruitment [10][11][12][13] . In contrast, mouse models of invasive Aspergillosis have revealed that CCL17 suppresses the anti-fungal response whereas CCL22 is involved in mediating fungal clearance [14] .…”
Section: Research Highlightmentioning
confidence: 99%